Internalisasi Qana’ah dalam Menghadapi Algoritma Marketplace: Studi Living Quran QS. Al- Furqan Ayat 67 terhadap Gaya Hidup Mahasiswa UIN Sumatera Utara - Maslan Nasution; Salahuddin Harahap (Kartika: Jurnal Studi Keislaman, 2026)
This study was motivated by the development of digital marketplace algorithms that influence students’ consumption patterns through product recommendations, digital promotions, and social media trends that encourage consumerist behavior. This study aims to analyze the internalization of the value of qana’ah in confronting the influence of marketplace algorithms on students in the Alquran and Tafsir Studies Program at UINSU through a living Quran approach to QS. Al-Furqan verse 67. This study employs a qualitative method using the living Quran approach. Data were collected through observation and in-depth interviews with five informants selected using purposive sampling. The results indicate that marketplace algorithms influence students’ consumer behavior through impulsive purchases and a tendency to follow digital trends. The internalization of the value of qana’ah occurs through the process of understanding, internalizing, and practicing the values of QS. Al-Furqan verse 67 in daily life. The implementation of the value of qana’ah is evident in students’ efforts to establish smart habits when using online marketplaces, distinguish between needs and wants, and curb digital consumerism. This study shows that the value of qana’ah serves as an economic, social, and spiritual check against consumerist culture in the era of digital marketplaces